Nine new species of Agromyzidae from North Carolina, USA, with new host and distribution records for additional species - Eiseman, Charles S.; Lonsdale, Owen; Feldman, Tracy S. (Zootaxa, 2019)
We present novel rearing records of Agromyzidae (Diptera) from three years of collecting in North Carolina, USA. These include the first reported host for Calycomyza novascotiensis Spencer (new to the USA) and new host records for Ophiomyia beckeri (Hendel) (new to North America), Liriomyza helianthi Spencer, L. schmidti (Aldrich), and Phytomyza plantaginis Robineau-Desvoidy, all of which are reported from North Carolina for the first time. We review host and distribution data for each of these species and describe their leaf mines. We describe the following nine new species: Agromyza arundinariae, A. indistincta, Calycomyza chrysopsidis, Cerodontha (Butomomyza) enigma, Cer. (Poemyza) arundinariella, Cer. (P.) saintandrewsensis, Liriomyza carphephori, L. polygalivora, and L. triodanidis. Seven host plant genera are new for world Agromyzidae: Carphephorus Cass., Chrysogonum L., Chrysopsis (Nutt.) Elliott, Krigia Schreb., Pyrrhopappus DC. (Asteraceae), Triodanis Raf. ex Greene (Campanulaceae), and Arundinaria Michx. s.s. (Poaceae). Host plants of the new species also include Bidens L., Mikania Willd. (Asteraceae), Dichanthelium (Hitchc. & Chase) Gould (Poaceae), and Polygala L. (Polygalaceae).